The degree of knowledge of teachers of students with learning disabilities in the primary stage of the computer skills of education in Riyadh - Al Omran, Suleiman Ibrahim (Journal of Educational and Psychological Sciences, 2017)
This study aimed to identify the degree of knowledge of students with learning difficulties in the primary stage in the computer skills in Riyadh and to identify the extent of the difference in the degree of knowledge of the computer skills of educational teachers of learning difficulties according to the variables of the study, and use the descriptive method. The results of the study were based on the approval of the sample of the study sample (4.12) from (5.00); high degree of knowledge of the teachers of learning difficulties in the primary stage of the computer skills in Riyadh, and the absence of statistically significant differences in the attitudes of the sample of the study about (The degree of knowledge of the teachers of learning difficulties in the primary stage of computer skills in the city of Riyadh) according to the variables of scientific qualification and variable years of experience and variable training courses in the field of computer. In the light of the results, a number of recommendations were made to increase teachers’ knowledge of the learning difficulties of this group of students.